1991
DOI: 10.1002/elan.1140030103
|View full text |Cite
|
Sign up to set email alerts
|

Silica gel modified carbon composite electrodes

Abstract: Carbon composite electrodes modified with silica gel exhibit properties analogous to those of an ultramicroelectrode array in voltammetric measurements. The limiting current in linear scan voltammetry is independent of the potential scan rate in certain scan rate regions. The possibility of using high potential scan rates is advantageous analytically, both in direct voltammetric determinations and in analyses involving accumulation of the analyte on the surface of the working electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In all case5 tlie hIFE were formed in situ after tlie addition of mercun(I1) ions into tlie measured solution. In a previous paper [3] There are not enough data to explain tlie low effect of oxigen on tlie dissolution of :ini:ilgams. In solutions containing dissolved oygen, tlie iZIFEmod yielded a signal that was tliree tinies higher than tlint of MFEconip (see Figure 1 ): in deaerated solutions tlie signal of the 1IFEniod increased by tlie factor 1 * 1 compared with t1i;it of the AlFEcomp.…”
Section: Mfe Formed On Surface Of Silica-gellcarbonmentioning
confidence: 91%
“…In all case5 tlie hIFE were formed in situ after tlie addition of mercun(I1) ions into tlie measured solution. In a previous paper [3] There are not enough data to explain tlie low effect of oxigen on tlie dissolution of :ini:ilgams. In solutions containing dissolved oygen, tlie iZIFEmod yielded a signal that was tliree tinies higher than tlint of MFEconip (see Figure 1 ): in deaerated solutions tlie signal of the 1IFEniod increased by tlie factor 1 * 1 compared with t1i;it of the AlFEcomp.…”
Section: Mfe Formed On Surface Of Silica-gellcarbonmentioning
confidence: 91%
“…Moreover, it was demonstrated that these electrodes behave similarly to a strand of carbon ultramicro-electrodes, allowing the analysis in dilute electrolyte solutions or even in the absence of electrolyte [59]. They were also advantageously applied to the anodic stripping voltammetric determination of low concentrations of silver, copper, lead and zinc [144]. In addition, the modified composite electrode was found to be stable in hydroorganic medium, even in the presence of great amounts of solvents, and displayed a good mechanical stability, enabling its use in flow systems.…”
Section: Pure Silica-based Electrodesmentioning
confidence: 98%
“…The pure silica-modified electrodes were only used to accumulate electroactive analytes (either by adsorption or ion exchange), in order to improve their amperometric detection [144][145][146][147][148][149][150]. In general, they exhibit similar background currents, double layer capacitance and metrological characteristics than those provided by the corresponding unmodified electrodes.…”
Section: Pure and Chemically Modified Silicasmentioning
confidence: 99%
See 1 more Smart Citation
“…Two electrochemical instruments, TRIBO 11-2 (Agricoop ValaSsko, Prague) with an X Y recorder XY 4103 (Laboratorni The following working electrodes were used: (i) a pen-type mercury electrode (Polaro-Sensors, Prague), (ii) a glassy carbon electrode (PAR, USA), and (iii) a silica gelmodified carbon paste electrode (12% silica gel, average particle size 30pm [36]). Such a composiite electrode has a very low background current and the anodic waves are better developed than for an unmodified carbon paste electrode [36]. The size of the static Hg drop was controlled by the valve opening value: for 0.1s, a drop with an area of 0.0041 cm2; and for 0.5 s, a drop with an area of 0.017cm2 was produced.…”
Section: Electrochemical Measurements and Instrumentationmentioning
confidence: 99%